2017
DOI: 10.1121/1.4974769
|View full text |Cite
|
Sign up to set email alerts
|

Consonant categorization exhibits a graded influence of surrounding spectral context

Abstract: When spectral properties differ across successive sounds, this difference is perceptually magnified, resulting in spectral contrast effects (SCEs). Recently, Stilp, Anderson, and Winn [(2015) J. Acoust. Soc. Am. 137(6), 3466–3476] revealed that SCEs are graded: more prominent spectral peaks in preceding sounds produced larger SCEs (i.e., category boundary shifts) in categorization of subsequent vowels. Here, a similar relationship between spectral context and SCEs was replicated in categorization of voiced sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 21 publications
6
38
0
Order By: Relevance
“…Not only were SCEs observed in nearly every condition tested, but their magnitudes varied continuously: As larger filter gains were tested, spectral differences between the context sentence and target vowel progressively increased, and SCE magnitudes increased in kind (see also Stilp & Alexander, 2016). This relationship was later replicated and extended in consonant categorization (Stilp & Assgari, 2017). Each of these studies reported strong linear relationships between filter gain (which introduced spectral differences between context and target sounds) and biases in speech categorization (i.e., SCEs magnitudes), supporting acute sensitivity to context when perceiving and categorizing speech sounds.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Not only were SCEs observed in nearly every condition tested, but their magnitudes varied continuously: As larger filter gains were tested, spectral differences between the context sentence and target vowel progressively increased, and SCE magnitudes increased in kind (see also Stilp & Alexander, 2016). This relationship was later replicated and extended in consonant categorization (Stilp & Assgari, 2017). Each of these studies reported strong linear relationships between filter gain (which introduced spectral differences between context and target sounds) and biases in speech categorization (i.e., SCEs magnitudes), supporting acute sensitivity to context when perceiving and categorizing speech sounds.…”
Section: Introductionmentioning
confidence: 91%
“…The magnitudes of SCEs vary continuously in speech categorization Stilp & Alexander, 2016;Stilp & Assgari, 2017), but it is unknown whether the same is true for SCEs influencing musical instrument categorization (as in Stilp et al, 2010). One possibility is that continuous variation in SCE magnitudes only occurs for highly familiar stimuli (e.g., speech).…”
Section: Introductionmentioning
confidence: 99%
“…Modest peaks produce modest SCEs. When there is a small change from context to the target, there is a smaller shift in categorization (Stilp, Anderson & Winn, 2015;Stilp & Assgari, 2017a). Detecting a decrease in an already modest effect requires more power.…”
Section: Limitationsmentioning
confidence: 99%
“…It has been established that SCEs are linear in nature: when the size of the change between the context and target increases, so does the shift in categorization Stilp & Alexander, 2016;Stilp & Assgari, 2017a). In these studies, the magnitude of the change from context to target to sentences was varied.…”
Section: Study 1 and 2 Synthesismentioning
confidence: 99%
See 1 more Smart Citation